2004
DOI: 10.1002/cncr.20165
|View full text |Cite
|
Sign up to set email alerts
|

Skip metastasis in nonsmall cell lung carcinoma

Abstract: BACKGROUND Skip metastasis to mediastinal lymph nodes is a prognostic factor for patients with nonsmall cell lung carcinoma (NSCLC). Little is known about the biologic behavior of tumors with noncontinuous spread to the mediastinal lymph nodes. In patients with pN2 skip metastases, micrometastases to N1 lymph nodes, which only mimic skip metastases, have not been investigated. METHODS In a retrospective study, the authors analyzed the primary tumor specimens from 45 patients with pN2 NSCLC (18 patients had squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In our series, the 5-year survival rate of the patients with skip-N2 disease was 33.4% despite complete resection with systematic lymphadenectomy Consistent with previous reports [1][2][3][4][5][6][7], survival of patients with non-skip-N2 disease was worse than that of patients with skip-N2 disease. The present study also showed that distant metastasis is the dominant cancer [25].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our series, the 5-year survival rate of the patients with skip-N2 disease was 33.4% despite complete resection with systematic lymphadenectomy Consistent with previous reports [1][2][3][4][5][6][7], survival of patients with non-skip-N2 disease was worse than that of patients with skip-N2 disease. The present study also showed that distant metastasis is the dominant cancer [25].…”
Section: Discussionsupporting
confidence: 91%
“…As the results of immnunohistochemical staining of N1 lymph nodes with anti-cytokeratin antibodies, one previous report indicated that microscopic spread of cancer cells could be detected in 17.6% of patients with skip-N2 disease [4]. Using immunohistochemical staining for cytokeratin in 3,081 lymph node samples obtained from 181 non-small cell lung cancer patients diagnosed as being in stage I by conventional histopathological examination, we previously found nodal micrometastasis in 44 patients [19].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our data suggested that a favorable prognosis might be obtained in spite of N2 disease, if subcarinal lymph node metastasis is not involved. The difference between these groups might be explained by the biological characteristics of the tumor that the node has [17]. In a study by Fujimoto et al, vascular endothelial cell growth factor (VEGF)-C levels were significantly (p < 0.05) increased in 24 of 40 metastatic lymph node lesions of uterine cervical cancers [18].…”
Section: Discussionmentioning
confidence: 94%